A tool for using the control of character animation to help teach children communication skills - Ying, Liangzhong (2012)
Effective Communication is an integral part of everyday life but recent studies show that in the UK many children fail to obtain this essential skill. The traditional approach to teaching communication skills is still important in school but new developments and the increasing availability of technology in the classroom, offer the potential for new ways to approach this teaching. A number of research institutions in the UK, for example the British Film Institute, are investigating how to use media such as films and television, in the classroom, in order to enhance children’s learning. Making cartoon films is a potentially valuable teaching approach but the lack of a suitable software tool to support this aspiration limits its viability. Existing software tools do reference the learning of communication skills as one of their features but they do not see this as a major learning objective.